ANALISA INDIKATOR MUTU PPI (PENCEGAHAN DAN PENGENDALIAN INFEKSI) UNIT RAWAT INAP DI RS X - Rosidin, Rona Qurrotul Aina; Aziz, Abdul; Subardi, Arda Yunita; Dwinuarisha, Eggie (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
The increasing incidence of HAIs has become an important problem in the world. The increased risk of HAIs infection is due to the lack of implementation of the IPC program, including implementing isolation precautions, implementing HAIs bundles and implementing surveillance. Nurses play an important role in preventing and controlling the transmission of infections through the implementation of standard precautions and maintenance of the Health care environment. The aim of this research is to carry out an analysis of quality indicators for Infection Prevention and Control so that priority problems can be found for which alternative solutions will be sought. The research design uses a qualitative approach through in-depth interviews, observations, and comparisons with ideal conditions based on the latest regulations. The research was conducted during the period May to July 2024. The results of examinations during the residency process found several problems, namely not optimal hand hygiene for officers (germs were found on the palms of the hands after Hand Hygiene), lack of compliance by officers in washing hands, lack of compliance with using PPE according to indications, lack of trained PPI team, found cases of HAIs Surgical Area Infection (SSI) and lack of reporting of cases of HAIs Phlebitis. Based on the priority assessment using the USG (Urgency, Seriousness and Growth) method, a priority problem was found, namely that the hand hygiene of staff was not optimal (germs were found on the palms of the hands after Hand Hygiene. Hospital in the treatment room.